Physiologic modifications during pregnancy - Purizaca Benites, Manuel (2015)
We present an updated review on the modifications and adaptation of the maternal organism to pregnancy, emphasizing their repercussions on complications during pregnancy. We also consider to know these modifications for therapeutic adjustments in case we need to administer medicines and drugs during the pregnancy.